Cerium-doped modified pre-sintered material, ferrite prepared by utilizing pre-sintered material, and preparation method and application of ferrite

By using hydrothermal reaction and wet ball milling processes to modify cerium-doped pre-sintered materials, the problems of particle size control and magnetic performance improvement in the preparation of permanent magnet ferrite pre-sintered materials were solved, achieving efficient and uniform ferrite preparation and improving magnetic performance.

CN121494525APending Publication Date: 2026-02-10SINOSTEEL ANHUI TIANYUAN TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202511805814.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-12-03
Publication Date
2026-02-10

AI Technical Summary

Technical Problem

In the existing technology, the preparation process of pre-sintered ferrite for permanent magnets has problems such as high cost and long time consumption for particle size control, difficulty in controlling the crystal growth direction, and insufficient magnetic properties.

Method used

A method for preparing cerium-doped modified pre-sintered material is adopted, in which micro-nuclei are generated through hydrothermal reaction and diffused at high temperature to form cerium-doped modified strontium ferrite. Combined with wet ball milling and sintering processes, the crystal growth direction is controlled to improve magnetic properties.

Benefits of technology

This method enables efficient preparation of pre-burned materials, improves remanence and saturation magnetization, enhances the magnetic coercivity and intrinsic coercivity of ferrites, and reduces the introduction of impurities and the inhomogeneity of particle size distribution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121494525A_ABST
    Figure CN121494525A_ABST
Patent Text Reader

Abstract

The invention discloses a cerium-doped modified pre-sintered material, ferrite prepared by using the pre-sintered material and a preparation method and application of the ferrite, and belongs to the technical field of permanent magnetic ferrites.The cerium-doped modified pre-sintered material is prepared by adopting a hydrothermal method, the dielectric constant of water is reduced and the ion product is increased at high temperature and high pressure, Fe < 3 + > can be promoted to be hydrolyzed to generate oxyhydroxide (alpha-FeOOH), and the performance of the ferrite is improved. Under the hydrothermal condition, alpha-FeOOH is converted into alpha-Fe2O3 after being dehydrated, Sr < 2 + > and Ce < 3 + > are diffused along alpha-Fe2O3 crystal lattice gaps through a solid-liquid interface diffusion mechanism, and finally the cerium-doped modified strontium ferrite is formed. Tiny crystal nucleuses obtained through the hydrothermal reaction can be deposited on the surfaces of large crystal grains, and stable nano-particles with the uniform size are formed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the technical field of permanent magnet ferrites, and particularly relates to a cerium-doped modified pre-sintered material, ferrites prepared using the pre-sintered material, and their preparation methods and applications. Technical Background

[0002] Ferrites, as a common magnetic functional material, play an important role in the entire magnetic materials system. They are generally composed of one or more metal oxides combined with Fe₂O₃, forming a ferromagnetic ceramic oxide with excellent performance and low cost. Currently, besides being used as permanent magnets, common applications include magnetic recording and data storage materials, as well as components in electronic devices and motor rotors. Ferrite permanent magnet materials are currently produced in large quantities, have a wide range of applications, and possess high commercial value.

[0003] Pre-sintered ferrite for permanent magnets is a key raw material in the production of permanent magnet ferrite materials. The performance of the pre-sintered material directly determines the performance level of the permanent magnet ferrite material. In particular, the average particle size and crystal growth direction of the pre-sintered material play a crucial role in the Br and Hcj properties of permanent magnet ferrites. Besides particle size, the performance of the pre-sintered material is also closely related to the formulation composition. To manufacture high-performance permanent magnet ferrite pre-sintered materials, it is necessary to refine single-domain particles to improve remanence and coercivity. Simultaneously, the grain size distribution also affects the degree of densification during the pre-sintering process. Therefore, fine particle size and uniform particle size distribution are indispensable for preparing high-performance pre-sintered materials.

[0004] In existing technologies, the main components of pre-sintered materials are strontium ferrite or barium ferrite, and they are typically prepared using ceramic processing methods (pre-sintering, crushing, molding, and sintering). For example, Chinese patent CN 110975996 A discloses a method for improving the grinding efficiency of pre-sintered permanent magnet ferrite materials. Before wet grinding, ferric chloride or ferrous chloride is added to the pre-sintered material, followed by wet grinding to obtain a slurry. During the grinding process, the pre-sintered permanent magnet ferrite powder gradually becomes finer, increasing the particle specific surface area and surface energy, leading to increased slurry viscosity and decreased flowability, thus reducing grinding efficiency. The ferric chloride or ferrous chloride added in this method can be adsorbed onto the surface of the slurry particles during grinding, significantly reducing the surface energy of the particles, overcoming inter-particle attraction, reducing crushing resistance, and improving slurry flowability, thereby increasing grinding efficiency. For example, Chinese patent CN 116178002A discloses a process for preparing strontium ferrite pre-sintered material. This involves vacuum melting with lanthanum oxide or alumina, followed by mixing and pressing with a curing agent, and then sintering to obtain the pre-sintered material. By sintering raw materials such as iron oxides and strontium oxides twice, the resulting pre-sintered material meets the requirements for density and magnetic properties. In these existing technologies, pre-sintered materials obtained through grinding and sintering or secondary sintering have two main drawbacks: firstly, the cost of particle size control is too high and the time required is too long, hindering mass production; secondly, the growth direction of the crystals in the pre-sintered material cannot be controlled, making it difficult to obtain high coercivity and remanence.

[0005] Therefore, researching a novel pre-sintered material preparation process to prepare ferrite using this pre-sintered material, thereby improving the magnetic properties of the product, has become a problem that needs to be solved. Summary of the Invention

[0006] The technical problem to be solved by the present invention is to provide a cerium-doped modified pre-sintered material, a ferrite prepared using the pre-sintered material, and a method for preparing and applying the same, so as to solve the problems mentioned in the background art or achieve better technical effects.

[0007] To solve the above-mentioned technical problems, the inventors derived the technical solution of this invention through practice and summarization. This invention discloses a cerium-doped modified pre-calcined material, in which the components are expressed in the following proportions by weight percentage: strontium nitrate 1.5~3%, cerium nitrate hexahydrate 1.5~2%, ferric nitrate nonahydrate 55~60%, citric acid 1~2%, and ammonia water 35~40%.

[0008] After the raw materials undergo a hydrothermal reaction at 150-200℃, they are dried and sintered at 1220-1280℃ to obtain cerium-doped modified pre-sintered material. The chemical formula of the pre-sintered material is Sr. (1-X) Ce X ·nFe2O3, (0.05≤X≤0.3, 5.5≤n≤6).

[0009] Furthermore, by weight percentage, the components are as follows: strontium nitrate 1.5%, cerium nitrate hexahydrate 1.6%, ferric nitrate nonahydrate 57.7%, citric acid 1%, and ammonia 38.2%;

[0010] After each raw material undergoes a hydrothermal reaction at 180℃, it is dried and sintered at 1230℃ to obtain cerium-doped modified pre-sintered material.

[0011] Furthermore, the preparation method of any of the above-mentioned cerium-doped modified pre-sintered materials includes the following steps:

[0012] S1: Strontium nitrate, cerium nitrate hexahydrate, ferric nitrate nonahydrate, citric acid, and ammonia are added to a PTFE reactor at 150-200℃ in a specific ratio. The hydrothermal reaction is carried out for 2-2.5 hours, followed by a holding time of 3.5-4 hours to obtain the hydrothermal product. Under high temperature and pressure, the dielectric constant of water decreases, and the ion product increases, which can promote the reaction of Fe... 3+ Hydrolysis produces hydroxyl oxides (α-FeOOH), which, under hydrothermal conditions, dehydrate to α-Fe₂O₃. Subsequently, through a solid-liquid interface diffusion mechanism, Sr... 2+ and Ce 3+ Cerium-doped strontium ferrite diffuses along the interstitial spaces of the α-Fe₂O₃ lattice, eventually forming cerium-doped modified strontium ferrite. The tiny nuclei obtained through hydrothermal reaction deposit on the surface of larger grains, forming uniform and relatively stable nanoparticles. 3+ The addition of [a specific ingredient] can regulate the growth direction of the crystal through steric hindrance, suppressing the growth of 2a, 12k, and 2b ferrite crystal planes, promoting the growth of 4f1 and 4f2 crystal planes, and reducing spin-up Fe [a specific ingredient]. 3+ This increases its remanence and saturation magnetization.

[0013] S2: Add ammonia to the hydrothermal product obtained in S1 to adjust the pH to 7, let stand for 5-6 hours, take the lower precipitate and dry it in a forced-air drying oven to obtain the precursor.

[0014] S3: Place the precursor obtained in step (2) in a muffle furnace at 1220℃~1280℃ and react for 3~4 hours. Cool to room temperature with the furnace to obtain cerium-doped modified pre-calcined material. Under specific high-temperature conditions, residual impurities in the precursor can be removed, ensuring the Sr... 2+ and Ce 3+ Uniform diffusion transforms the precursor into a magnetic M-type ferrite, promoting crystal growth and increasing Br.

[0015] Furthermore, a ferrite, using any of the cerium-doped modified pre-sintered materials described above as the pre-sintered material, has the following component proportions by weight percentage:

[0016] The pre-burned material contains 92-98% strontium carbonate, 0.8%-1.0% strontium carbonate, 0.14%-0.35% alumina, 1.5%-2.5% lanthanum oxide, 0.6%-1.2% cobalt oxide, 0.3%-0.5% boric acid, 0.3%-0.5% barium carbonate, and 0.1%-0.2% silicon dioxide.

[0017] The strontium carbonate has a purity of ≥99.5%, the alumina has a purity of ≥99%, the lanthanum oxide has a purity of ≥99.3%, the cobalt oxide has a purity of ≥99.9%, the boric acid has a purity of ≥99%, and the barium carbonate has a purity of ≥99.5%.

[0018] Furthermore, the percentages of each component by weight are as follows:

[0019] The pre-burned feedstock contains 95.76% strontium carbonate, 0.9% alumina, 0.14% lanthanum oxide, 2% cobalt oxide, 0.5% boric acid, 0.3% barium carbonate, and 0.1% silicon dioxide.

[0020] Furthermore, the preparation method of any of the above-mentioned ferrites includes the following steps:

[0021] S1: Mix the pre-burned material and auxiliary materials according to the ratio, add them to a ball mill for ball milling, and obtain a slurry with a particle size of 0.63~0.7μm;

[0022] S2: The slurry obtained in S1 is dehydrated by a centrifugal dewatering machine to maintain the moisture content of the slurry at 30-35%. The slurry is then pressed and oriented to obtain a green body.

[0023] S3: Place the billet obtained in S2 into a pusher kiln and sinter it at 1200~1220℃ for 45~60 minutes, then cool it with the furnace to obtain ferrite.

[0024] Furthermore, in S1, a wet ball milling process is adopted. The wet ball milling process is as follows: after the pre-burned material and auxiliary materials are mixed and added to the ball mill, water is added to the ball mill to keep the moisture content of the entire slurry system at 65~70%, and the mixture is ball-milled with bearing steel balls for 5~6 hours.

[0025] Furthermore, in S2, during the pressing and orientation forming process, filtration is carried out with a filter cloth to keep the moisture content of the formed blank at 10~15%.

[0026] Furthermore, in S3, the sintering temperature is 1210℃ and the sintering time is 45min.

[0027] Furthermore, the application of any of the aforementioned ferrites in permanent magnet materials.

[0028] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0029] (1) In this invention, cerium nitrate hexahydrate is introduced into the raw materials to modify and prepare ferrite pre-calcined materials, accompanied by Ce 3+ The addition of [a specific ingredient] can regulate the growth direction of the crystal through steric hindrance, suppressing the growth of 2a, 12k, and 2b ferrite crystal planes, promoting the growth of 4f1 and 4f2 crystal planes, and reducing spin-up Fe [a specific ingredient]. 3+ This will enhance the remanence and saturation magnetization of the product.

[0030] (2) In the preparation process of the pre-sintered material, the present invention uses a hydrothermal method to prepare cerium-doped modified pre-sintered material. Under high temperature and high pressure, the dielectric constant of water decreases and the ion product increases, which can promote the Fe... 3+ Hydrolysis produces hydroxyl oxides (α-FeOOH), which, under hydrothermal conditions, dehydrate to α-Fe₂O₃. Subsequently, through a solid-liquid interface diffusion mechanism, Sr... 2+ and Ce 3+ The cerium-doped modified strontium ferrite diffuses along the interstitial spaces of the α-Fe2O3 lattice and eventually forms a cerium-doped modified strontium ferrite. The tiny nuclei obtained through the hydrothermal reaction are deposited on the surface of larger grains to form uniform and relatively stable nanoparticles.

[0031] (3) The hydrothermal product prepared by the present invention is subjected to pH adjustment and drying to obtain a precursor. This precursor can remove residual impurities in the precursor under a specific high temperature environment of 1220~1280℃, ensuring the quality of Sr. 2+ and Ce 3+ Uniform diffusion transforms the precursor into a magnetic M-type ferrite, promoting crystal growth and increasing Br.

[0032] (4) In this invention, after the pre-calcined material is prepared by hydrothermal method, it is compounded with relevant auxiliary materials, and then ball milling is carried out by wet milling process to control the moisture content of the whole system at 65~70%. Compared with dry method, ball milling has higher efficiency, finer particle size and narrower particle size distribution, smaller friction coefficient, less impurities introduced and higher purity.

[0033] (5) Before the slurry is pressed and molded, the water content of the slurry is controlled to be 30-35% through a dehydration process. It has a certain fluidity to facilitate pressing and molding, and also has a certain green strength to avoid cracking and delamination during the pressing process. During the pressing process, the arrangement of grains in the slurry can be improved by pre-magnetization orientation, and the internal magnetic domain orientation can be fixed. Attached Figure Description

[0034] Figure 1 XRD pattern of the pre-burned material prepared in Example 1;

[0035] Figure 2 This is a scanning electron microscope image of the ferrite prepared in Example 4 of the present invention. Detailed Implementation

[0036] To make the above-mentioned objectives, features and advantages of the present invention more apparent and understandable, the specific embodiments of the present invention will be described in detail below with reference to specific examples.

[0037] Unless otherwise specified, the raw materials or reagents used in the following examples and comparative examples are commercially available products or products prepared using conventional techniques.

[0038] Among them, the purity of strontium carbonate is ≥99.5%, the purity of aluminum oxide is ≥99%, the purity of lanthanum oxide is ≥99.3%, the purity of cobalt oxide is ≥99.9%, the purity of boric acid is ≥99%, and the purity of barium carbonate is ≥99.5%.

[0039] The ball mill used in the following embodiments is a QMZ2100X2100 magnetic ball mill.

[0040] A cerium-doped modified pre-sintered material, with the following component proportions by weight percentage:

[0041] Strontium nitrate 1.5-3%, cerium nitrate hexahydrate 1.5-2%, ferric nitrate nonahydrate 55-60%, citric acid 1-2%, and ammonia 35-40%;

[0042] The preparation method of the above-mentioned pre-fired material includes the following steps:

[0043] (1) Strontium nitrate, cerium nitrate hexahydrate, ferric nitrate nonahydrate, citric acid, and ammonia water are added to a PTFE reactor at 150-200℃ in a certain ratio. The hydrothermal reaction is carried out for 2-2.5 hours and then kept at the temperature for 3.5-4 hours to obtain the hydrothermal product. Under high temperature and high pressure, the dielectric constant of water decreases and the ion product increases, which can promote the reaction of Fe. 3+ Hydrolysis produces hydroxyl oxides (α-FeOOH), which, under hydrothermal conditions, dehydrate to α-Fe₂O₃. Subsequently, through a solid-liquid interface diffusion mechanism, Sr... 2+ and Ce 3+ Cerium-doped strontium ferrite diffuses along the interstitial spaces of the α-Fe₂O₃ lattice, eventually forming cerium-doped modified strontium ferrite. The tiny nuclei obtained through hydrothermal reaction deposit on the surface of larger grains, forming uniform and relatively stable nanoparticles. 3+ The addition of [a specific ingredient] can regulate the growth direction of the crystal through steric hindrance, suppressing the growth of 2a, 12k, and 2b ferrite crystal planes, promoting the growth of 4f1 and 4f2 crystal planes, and reducing spin-up Fe [a specific ingredient]. 3+ This increases its remanence and saturation magnetization.

[0044] (2) Add ammonia to the hydrothermal product obtained in step (1) to adjust the pH to 7, let it stand for 5-6 hours, take the lower precipitate and dry it in a forced-air drying oven to obtain the precursor;

[0045] (3) Place the precursor obtained in step (2) in a muffle furnace at 1220℃~1280℃ and react for 3~4 hours. Under a specific high-temperature environment, the residual impurities in the precursor can be removed, ensuring the Sr 2+ and Ce 3+ Uniform diffusion transforms the precursor into a magnetic M-type ferrite, promoting crystal growth and increasing Br content. Cooling to room temperature in the furnace yields a pre-sintered material with the chemical formula Sr. (1-X) Ce X ·nFe2O3, (0.05≤X≤0.3, 5.5≤n≤6);

[0046] The ferrite prepared using the above pre-sintered material has the following component percentages by weight:

[0047] The composition of the pre-burned feedstock is as follows: 92-98% strontium carbonate, 0.8-1.0% strontium carbonate, 0.14-0.35% alumina, 1.5-2.5% lanthanum oxide, 0.6-1.2% cobalt oxide, 0.3-0.5% boric acid, 0.3-0.5% barium carbonate, and 0.1-0.2% silicon dioxide.

[0048] The preparation method of the above ferrite is as follows:

[0049] (1) The pre-calcined material and auxiliary materials are mixed according to the formula and added to the ball mill. Water is then added to maintain the moisture content of the entire slurry system at 65-70%. The slurry is ball-milled with bearing steel balls for 5-6 hours to obtain a slurry with a particle size of 0.63-0.7μm. Compared with dry ball milling, wet ball milling has higher efficiency, finer particle size and narrower particle size distribution, lower friction coefficient, fewer impurities introduced, and higher purity. If the moisture content is too high, the ball milling efficiency will decrease, and the ball milling time will increase the loss. If the moisture content is too low, more impurities will be introduced into the ball mill, and the purity of the slurry will decrease.

[0050] (2) The slurry obtained in step (1) is dehydrated by a centrifugal dewatering machine to maintain the moisture content of the slurry at 30-35%. When the moisture content is too high, the molding process is difficult and the green strength is too low. When the moisture content is too low, the fluidity of the slurry is too low. During molding, a series of problems such as cracking and delamination will occur. Pre-magnetization can improve the arrangement of grains in the slurry and fix the internal magnetic domain orientation. Then the slurry is pressed and oriented. During the pressing process, the slurry is filtered with a filter cloth to keep the moisture content of the molded green body at 10-15%.

[0051] (3) Place the billet obtained in step (2) into a pusher kiln and sinter it at 1200~1220℃ for 45~60min to eliminate pores, make the ferrite dense, repair lattice defects, reduce single-domain particles, and make the composition more uniform. Then cool it with the furnace to obtain ferrite.

[0052] Example 1

[0053] A cerium-doped modified pre-sintered material, with the following component proportions by weight percentage:

[0054] Strontium nitrate 1.5%, cerium nitrate hexahydrate 1.6%, ferric nitrate nonahydrate 57.7%, citric acid 1%, and ammonia 38.2%.

[0055] The preparation method of the above-mentioned pre-fired material includes the following steps:

[0056] (1) Strontium nitrate, cerium nitrate hexahydrate, ferric nitrate nonahydrate, citric acid and ammonia water were added to a PTFE reactor at 180°C in proportion, and the hydrothermal reaction was carried out for 2 hours and kept at the temperature for 4 hours to obtain the hydrothermal product.

[0057] (2) Add ammonia to the hydrothermal product obtained in step (1) to adjust the pH to 7, let it stand for 5 hours, take the lower precipitate and dry it in a forced-air drying oven to obtain the precursor;

[0058] (3) The precursor obtained in step (2) was placed in a muffle furnace at 1230℃ and reacted for 3 hours. After cooling to room temperature with the furnace, the pre-calcined material was obtained. The XRD pattern is shown in the figure. Figure 1 As shown.

[0059] Example 2

[0060] A cerium-doped modified pre-sintered material, with the following component proportions by weight percentage:

[0061] Strontium nitrate 2%, cerium nitrate hexahydrate 2%, ferric nitrate nonahydrate 56.8%, citric acid 1%, and ammonia 38.2%.

[0062] The preparation method of the above-mentioned pre-fired material includes the following steps:

[0063] (1) Strontium nitrate, cerium nitrate hexahydrate, ferric nitrate nonahydrate, citric acid and ammonia water were added to a PTFE reactor at 180℃ in proportion, and the hydrothermal reaction was carried out for 2 hours and kept at the temperature for 4 hours to obtain the hydrothermal product.

[0064] (2) Add ammonia to the hydrothermal product obtained in step (1) to adjust the pH to 7, let it stand for 5 hours, take the lower precipitate and dry it in a forced-air drying oven to obtain the precursor;

[0065] (3) The precursor obtained in step (2) is placed in a muffle furnace at 1230℃ and reacted for 3 hours. The furnace is then cooled to room temperature to obtain the pre-burned material.

[0066] Example 3

[0067] A cerium-doped modified pre-sintered material, with the following component proportions by weight percentage:

[0068] Strontium nitrate 2%, cerium nitrate hexahydrate 1.8%, ferric nitrate nonahydrate 57.7%, citric acid 1%, and ammonia 37.5%.

[0069] The preparation method of the above-mentioned pre-fired material includes the following steps:

[0070] (1) Strontium nitrate, cerium nitrate hexahydrate, ferric nitrate nonahydrate, citric acid and ammonia water were added to a PTFE reactor at 180℃ in proportion, and the hydrothermal reaction was carried out for 2 hours and kept at the temperature for 4 hours to obtain the hydrothermal product.

[0071] (2) Add ammonia to the hydrothermal product obtained in step (1) to adjust the pH to 7, let it stand for 5 hours, take the lower precipitate and dry it in a forced-air drying oven to obtain the precursor;

[0072] (3) Place the precursor obtained in step (2) in a muffle furnace at 1230℃ and react for 3 hours. Then cool it to room temperature with the furnace to obtain the pre-burned material.

[0073] Example 4

[0074] The ferrite prepared using the pre-sintered material obtained in Example 1 has the following component percentages by weight:

[0075] The pre-burned feedstock contains 95.76% strontium carbonate, 0.9% alumina, 0.14% lanthanum oxide, 2% cobalt oxide, 0.5% boric acid, 0.3% barium carbonate, and 0.1% silicon dioxide.

[0076] The preparation method of the above ferrite is as follows:

[0077] (1) Mix the pre-burned material and auxiliary materials according to the ratio, add them to the ball mill, and then add water to keep the moisture content of the entire slurry system at 65~70%. After ball milling with bearing steel balls for 5~6 hours, a slurry with a particle size of 0.63~0.7μm is obtained.

[0078] (2) The slurry obtained in step (1) is dehydrated by a centrifugal dewatering machine to maintain the moisture content of the slurry at 30-35%. Then the slurry is pressed and oriented. During the pressing process, the slurry is filtered with a filter cloth to keep the moisture content of the shaped blank at 10-15%.

[0079] (3) Place the billet obtained in step (2) into a pusher kiln and sinter at 1210℃ for 45~60 min, then cool it with the furnace to obtain ferrite, the microstructure of which is as follows. Figure 2 As shown.

[0080] Example 5

[0081] The ferrite prepared using the pre-calcined material obtained in Example 2 has the following component percentages by weight:

[0082] The pre-burned feedstock contains 95.76% strontium carbonate, 0.9% alumina, 0.14% lanthanum oxide, 2% cobalt oxide, 0.5% boric acid, 0.3% barium carbonate, and 0.1% silicon dioxide.

[0083] The preparation method of the above ferrite is as follows:

[0084] (1) Mix the pre-burned material and auxiliary materials according to the ratio, add them to the ball mill, and then add water to keep the moisture content of the entire slurry system at 65~70%. After ball milling with bearing steel balls for 5~6 hours, a slurry with a particle size of 0.63~0.7μm is obtained.

[0085] (2) The slurry obtained in step (1) is dehydrated by a centrifugal dewatering machine to maintain the moisture content of the slurry at 30-35%. Then the slurry is pressed and oriented. During the pressing process, the slurry is filtered with a filter cloth to keep the moisture content of the shaped blank at 10-15%.

[0086] (3) Place the billet obtained in step (2) into a pusher kiln and sinter it at 1210℃ for 45 minutes. Then cool it with the furnace to obtain ferrite.

[0087] Example 6

[0088] The ferrite prepared using the pre-sintered material obtained in Example 3 has the following component percentages by weight:

[0089] The pre-burned feedstock contains 95.76% strontium carbonate, 0.9% alumina, 0.14% lanthanum oxide, 2% cobalt oxide, 0.5% boric acid, 0.3% barium carbonate, and 0.1% silicon dioxide.

[0090] The preparation method of the above ferrite is as follows:

[0091] (1) Mix the pre-burned material and auxiliary materials according to the ratio, add them to the ball mill, and then add water to keep the moisture content of the entire slurry system at 65~70%. After ball milling with bearing steel balls for 5~6 hours, a slurry with a particle size of 0.63~0.7μm is obtained.

[0092] (2) The slurry obtained in step (1) is dehydrated by a centrifugal dewatering machine to maintain the moisture content of the slurry at 30-35%. Then the slurry is pressed and oriented. During the pressing process, the slurry is filtered with a filter cloth to keep the moisture content of the shaped blank at 10-15%.

[0093] (3) Place the billet obtained in step (2) into a pusher kiln and sinter it at 1210℃ for 45 minutes. Then cool it with the furnace to obtain ferrite.

[0094] Example 7

[0095] The ferrite prepared using the pre-sintered material obtained in Example 1 has the following component percentages by weight:

[0096] The pre-burned feedstock contains 98.27% strontium carbonate, 0.6% alumina, 0.05% lanthanum oxide, 0.5% cobalt oxide, 0.2% boric acid, 0.15% barium carbonate, and 0.08% silicon dioxide.

[0097] The preparation method of the above ferrite is as follows:

[0098] (1) Mix the pre-burned material and auxiliary materials according to the ratio, add them to the ball mill, and then add water to keep the moisture content of the entire slurry system at 65~70%. After ball milling with bearing steel balls for 5~6 hours, a slurry with a particle size of 0.63~0.7μm is obtained.

[0099] (2) The slurry obtained in step (1) is dehydrated by a centrifugal dewatering machine to maintain the moisture content of the slurry at 30-35%. Then the slurry is pressed and oriented. During the pressing process, the slurry is filtered with a filter cloth to keep the moisture content of the shaped blank at 10-15%.

[0100] (3) Place the billet obtained in step (2) into a pusher kiln and sinter it at 1210℃ for 45 minutes. Then cool it with the furnace to obtain ferrite.

[0101] Example 8

[0102] The ferrite prepared using the pre-sintered material obtained in Example 1 has the following component percentages by weight:

[0103] The composition of the pre-burned feedstock is 91.45%, strontium carbonate 1.2%, alumina 0.4%, lanthanum oxide 3%, cobalt oxide 1.5%, boric acid 0.55%, barium carbonate 0.6%, and silicon dioxide 0.3%.

[0104] The preparation method of the above ferrite is as follows:

[0105] (1) Mix the pre-burned material and auxiliary materials according to the ratio, add them to the ball mill, and then add water to keep the moisture content of the entire slurry system at 65~70%. After ball milling with bearing steel balls for 5~6 hours, a slurry with a particle size of 0.63~0.7μm is obtained.

[0106] (2) The slurry obtained in step (1) is dehydrated by a centrifugal dewatering machine to maintain the moisture content of the slurry at 30-35%. Then the slurry is pressed and oriented. During the pressing process, the slurry is filtered with a filter cloth to keep the moisture content of the shaped blank at 10-15%.

[0107] (3) Place the billet obtained in step (2) into a pusher kiln and sinter it at 1210℃ for 45 minutes. Then cool it with the furnace to obtain ferrite.

[0108] Comparative Example 1

[0109] A cerium-doped modified pre-sintered material, with the following component proportions by weight percentage:

[0110] Strontium nitrate 4.1%, ferric nitrate nonahydrate 57.7%, citric acid 1%, and ammonia 38.2%.

[0111] The preparation method of the above-mentioned pre-fired material includes the following steps:

[0112] (1) Strontium nitrate, cerium nitrate hexahydrate, ferric nitrate nonahydrate, citric acid and ammonia water were added to a PTFE reactor at 180℃ in proportion, and the hydrothermal reaction was carried out for 2 hours and kept at the temperature for 4 hours to obtain the hydrothermal product.

[0113] (2) Add ammonia to the hydrothermal product obtained in step (1) to adjust the pH to 7, let it stand for 5 hours, take the lower precipitate and dry it in a forced-air drying oven to obtain the precursor;

[0114] (3) The precursor obtained in step (2) is placed in a muffle furnace at 1230℃ and reacted for 3 hours. The furnace is then cooled to room temperature to obtain the pre-burned material.

[0115] The ferrite prepared using pre-sintered materials has the following component percentages by weight:

[0116] Pre-fired feedstock 95.76 % Strontium carbonate 0.9%; aluminum oxide 0.14%; lanthanum oxide 2%; cobalt oxide 0.5%; boric acid 0.3%; barium carbonate 0.3%; silicon dioxide 0.1%;

[0117] The preparation method of the above ferrite is as follows:

[0118] (1) Mix the pre-burned material and auxiliary materials according to the ratio, add them to the ball mill, and then add water to keep the moisture content of the entire slurry system at 65~70%. After ball milling with bearing steel balls for 5~6 hours, a slurry with a particle size of 0.63~0.7μm is obtained.

[0119] (2) The slurry obtained in step (1) is dehydrated by a centrifugal dewatering machine to maintain the moisture content of the slurry at 30-35%. (The slurry is then pressed and oriented. During the pressing process, it is filtered with a filter cloth to keep the moisture content of the shaped blank at 10-15%.)

[0120] (3) Place the billet obtained in step (2) into a pusher kiln and sinter it at 1210°C for 45 minutes. Then cool it with the furnace to obtain ferrite.

[0121] Comparative Example 2

[0122] A cerium-doped modified pre-sintered material, with the following component proportions by weight percentage:

[0123] Strontium nitrate 0.9%, cerium nitrate hexahydrate 1.2%, ferric nitrate nonahydrate 57.7%, citric acid 1%, and ammonia 38.2%.

[0124] The preparation method of the above-mentioned pre-fired material includes the following steps:

[0125] (1) Strontium nitrate, cerium nitrate hexahydrate, ferric nitrate nonahydrate, citric acid and ammonia water were added to a PTFE reactor at 180℃ in proportion, and the hydrothermal reaction was carried out for 2 hours and kept at the temperature for 4 hours to obtain the hydrothermal product.

[0126] (2) Add ammonia to the hydrothermal product obtained in step (1) to adjust the pH to 7, let it stand for 5 hours, take the lower precipitate and dry it in a forced-air drying oven to obtain the precursor;

[0127] (3) The precursor obtained in step (2) is placed in a muffle furnace at 1230℃ and reacted for 3 hours. The furnace is then cooled to room temperature to obtain the pre-burned material.

[0128] The ferrite prepared using pre-sintered materials has the following component percentages by weight:

[0129] The pre-burned feedstock contains 95.76% strontium carbonate, 0.9% alumina, 0.14% lanthanum oxide, 2% cobalt oxide, 0.5% boric acid, 0.3% barium carbonate, and 0.1% silicon dioxide.

[0130] The preparation method of the above ferrite is as follows:

[0131] (1) Mix the pre-burned material and auxiliary materials according to the ratio, add them to the ball mill, and then add water to keep the moisture content of the entire slurry system at 65~70%. After ball milling with bearing steel balls for 5~6 hours, a slurry with a particle size of 0.63~0.7μm is obtained.

[0132] (2) The slurry obtained in step (1) is dehydrated by a centrifugal dewatering machine to maintain the moisture content of the slurry at 30-35%. Then the slurry is pressed and oriented. During the pressing process, the slurry is filtered with a filter cloth to keep the moisture content of the shaped blank at 10-15%.

[0133] (3) Place the billet obtained in step (2) into a pusher kiln and sinter it at 1210℃ for 45 minutes. Then cool it with the furnace to obtain ferrite.

[0134] Comparative Example 3

[0135] A cerium-doped modified pre-sintered material, with the following component proportions by weight percentage:

[0136] Strontium nitrate 1.6%, cerium nitrate hexahydrate 2.5%, ferric nitrate nonahydrate 57.7%, citric acid 1%, and ammonia 38.2%.

[0137] The preparation method of the above-mentioned pre-fired material includes the following steps:

[0138] (1) Strontium nitrate, cerium nitrate hexahydrate, ferric nitrate nonahydrate, citric acid and ammonia water were added to a PTFE reactor at 180℃ in proportion, and the hydrothermal reaction was carried out for 2 hours and kept at the temperature for 4 hours to obtain the hydrothermal product.

[0139] (2) Add ammonia to the hydrothermal product obtained in step (1) to adjust the pH to 7, let it stand for 5 hours, take the lower precipitate and dry it in a forced-air drying oven to obtain the precursor;

[0140] (3) The precursor obtained in step (2) is placed in a muffle furnace at 1230℃ and reacted for 3 hours. The furnace is then cooled to room temperature to obtain the pre-burned material.

[0141] The ferrite prepared using pre-sintered materials has the following component percentages by weight:

[0142] The pre-burned feedstock contains 95.76% strontium carbonate, 0.9% alumina, 0.14% lanthanum oxide, 2% cobalt oxide, 0.5% boric acid, 0.3% barium carbonate, and 0.1% silicon dioxide.

[0143] The preparation method of the above ferrite is as follows:

[0144] (1) Mix the pre-burned material and auxiliary materials according to the ratio, add them to the ball mill, and then add water to keep the moisture content of the entire slurry system at 65~70%. After ball milling with bearing steel balls for 5~6 hours, a slurry with a particle size of 0.63~0.7μm is obtained.

[0145] (2) The slurry obtained in step (1) is dehydrated by a centrifugal dewatering machine to maintain the moisture content of the slurry at 30-35%. Then the slurry is pressed and oriented. During the pressing process, the slurry is filtered with a filter cloth to keep the moisture content of the shaped blank at 10-15%.

[0146] (3) Place the billet obtained in step (2) into a pusher kiln and sinter it at 1210℃ for 45 minutes. Then cool it with the furnace to obtain ferrite.

[0147] Comparative Example 4

[0148] A cerium-doped modified pre-sintered material, with the following component proportions by weight percentage:

[0149] Iron oxide red 87.2%, Strontium carbonate 6.3%, Cerium carbonate 6.5%

[0150] The preparation method of the above-mentioned pre-fired material includes the following steps:

[0151] (1). Add iron oxide red strontium carbonate and cerium carbonate to a sand mill according to the specified ratio and mix for 2 hours;

[0152] (2). Mixing and sintering: The mixture is pelletized and sintered at a temperature of 1230℃ for 3 hours.

[0153] (3) Crushing the pre-fired material: 1% sorbitol dispersant was added to the sintered pellets and crushed to obtain the pre-fired material.

[0154] The ferrite prepared using pre-sintered materials has the following component percentages by weight:

[0155] The pre-burned feedstock contains 95.76% strontium carbonate, 0.9% alumina, 0.14% lanthanum oxide, 2% cobalt oxide, 0.5% boric acid, 0.3% barium carbonate, and 0.1% silicon dioxide.

[0156] The preparation method of the above ferrite is as follows:

[0157] (1) Mix the pre-burned material and auxiliary materials according to the ratio, add them to the ball mill, and then add water to keep the moisture content of the entire slurry system at 65~70%. After ball milling with bearing steel balls for 5~6 hours, a slurry with a particle size of 0.63~0.7μm is obtained.

[0158] (2) The slurry obtained in step (1) is dehydrated by a centrifugal dewatering machine to maintain the moisture content of the slurry at 30-35%. Then the slurry is pressed and oriented. During the pressing process, the slurry is filtered with a filter cloth to keep the moisture content of the shaped blank at 10-15%.

[0159] (3) Place the billet obtained in step (2) into a pusher kiln and sinter it at 1210℃ for 45 minutes. Then cool it with the furnace to obtain ferrite.

[0160] The ferrites prepared in Examples 4-8 and Comparative Examples 1-4 were subjected to remanence B tests. r (mT), magnetic coercivity H cb (kA / m), intrinsic coercivity H cj (kA / m) and maximum energy product (BH) max (kJ / m 3 The magnetic properties were tested using an NIM-62000 instrument, and the test data are shown in Table 1 below.

[0161] Table 1. Magnetic properties of ferrites prepared in Examples 4-8 and Comparative Examples 1-4

[0162]

[0163] Analysis of Table 1 shows that, compared to Comparative Examples 1-4, the ferrite products prepared in Examples 4-8 exhibit significantly better magnetic coercivity and intrinsic coercivity. This is because, during the hydrothermal reaction, α-FeOOH dehydrates and transforms into α-Fe2O3, which then diffuses through the solid-liquid interface, allowing Sr... 2+ and Ce 3+ Cerium-doped strontium ferrite diffuses along the interstitial spaces of the α-Fe₂O₃ lattice, eventually forming cerium-doped modified strontium ferrite. The tiny nuclei obtained through hydrothermal reaction deposit on the surface of larger grains, forming uniform and relatively stable nanoparticles. 3+ The addition of [a specific ingredient] can regulate the growth direction of the crystal through steric hindrance, suppressing the growth of 2a, 12k, and 2b ferrite crystal planes, promoting the growth of 4f1 and 4f2 crystal planes, and reducing spin-up Fe [a specific ingredient]. 3+ This will enhance its remanence and saturation magnetization.

[0164] A comparison of Example 4 and Comparative Example 3 shows that when the proportion of cerium nitrate hexahydrate added to the pre-calcined feed formulation exceeds the specified range, Ce... 3+ When the water becomes saturated, cerium oxide crystals are formed, which in turn reduces the magnetic properties.

[0165] A comparison between Example 4 and Comparative Example 1 shows that Ce 3+ The introduction of [a specific element] regulates the crystal growth direction through steric hindrance, inhibiting the growth of 2a, 12k, and 2b, promoting the growth of 4f1 and 4f2, and reducing spin-up Fe [a specific element]. 3+ It can refine the grains and enhance the anisotropy of the grains, thereby improving its magnetic properties.

[0166] A comparison of Example 4 and Comparative Example 4 shows that the pre-calcined material synthesized by the hydrothermal method has higher performance, especially in terms of its Hcj properties. This indicates that the tiny crystal nuclei obtained through the hydrothermal reaction will deposit on the surface of larger grains, forming uniform and relatively stable nanoparticles, refining the grains, improving their orientation, and thus enhancing performance.

Claims

1. A cerium-doped modified pre-sintered material, characterized in that, The components, by weight percentage, are as follows: strontium nitrate 1.5-3%, cerium nitrate hexahydrate 1.5-2%, ferric nitrate nonahydrate 55-60%, citric acid 1-2%, and ammonia 35-40%; After the raw materials undergo a hydrothermal reaction at 150-200℃, they are dried and sintered at 1220-1280℃ to obtain cerium-doped modified pre-sintered material. The chemical formula of the pre-sintered material is Sr. (1-X) Ce X ·nFe2O3, (0.05≤X≤0.3, 5.5≤n≤6).

2. The cerium-doped modified pre-sintered material according to claim 1, characterized in that, The components, by weight percentage, are as follows: strontium nitrate 1.5%, cerium nitrate hexahydrate 1.6%, ferric nitrate nonahydrate 57.7%, citric acid 1%, and ammonia 38.2%; After the raw materials undergo a hydrothermal reaction at 180℃, they are dried and sintered at 1230℃ to obtain cerium-doped modified pre-sintered material.

3. A method for preparing cerium-doped modified pre-sintered material as described in claim 1 or 2, characterized in that, The steps are as follows: S1: Strontium nitrate, cerium nitrate hexahydrate, ferric nitrate nonahydrate, citric acid and ammonia water are added to a PTFE reactor at 150~200℃ in a certain proportion. The hydrothermal reaction is carried out for 2~2.5h and then kept at the temperature for 3.5~4h to obtain the hydrothermal product. S2: Add ammonia to the hydrothermal product obtained in S1 to adjust the pH to 7, let stand for 5-6 hours, take the lower precipitate and dry it in a forced-air drying oven to obtain the precursor. S3: Place the precursor obtained in step (2) in a muffle furnace at 1220℃~1280℃ and react for 3~4 hours. Then cool it to room temperature with the furnace to obtain cerium-doped modified pre-burned material.

4. A ferrite, characterized in that, Using the cerium-doped modified pre-sintered material according to any one of claims 1 to 2 as the pre-sintered material, the proportions of each component by weight percentage are as follows: The pre-burned material contains 92-98% strontium carbonate, 0.8%-1.0% strontium carbonate, 0.14%-0.35% alumina, 1.5%-2.5% lanthanum oxide, 0.6%-1.2% cobalt oxide, 0.3%-0.5% boric acid, 0.3%-0.5% barium carbonate, and 0.1%-0.2% silicon dioxide. The strontium carbonate has a purity of ≥99.5%, the alumina has a purity of ≥99%, the lanthanum oxide has a purity of ≥99.3%, the cobalt oxide has a purity of ≥99.9%, the boric acid has a purity of ≥99%, and the barium carbonate has a purity of ≥99.5%.

5. The ferrite according to claim 4, characterized in that, The percentages of each component by weight are as follows: The pre-burned feedstock contains 95.76% strontium carbonate, 0.9% alumina, 0.14% lanthanum oxide, 2% cobalt oxide, 0.5% boric acid, 0.3% barium carbonate, and 0.1% silicon dioxide.

6. A method for preparing the ferrite as described in any one of claims 4 or 5, characterized in that, The steps are as follows: S1: Mix the pre-burned material and auxiliary materials according to the ratio, add them to a ball mill for ball milling, and obtain a slurry with a particle size of 0.63~0.7μm; S2: The slurry obtained in S1 is dehydrated by a centrifugal dewatering machine to maintain the moisture content of the slurry at 30-35%. The slurry is then pressed and oriented to obtain a green body. S3: Place the billet obtained in S2 into a pusher kiln and sinter it at 1200~1220℃ for 45~60 minutes, then cool it with the furnace to obtain ferrite.

7. The method for preparing ferrite according to claim 6, characterized in that, In S1, a wet ball milling process is adopted. The wet ball milling process is as follows: after the pre-burned material and auxiliary materials are mixed and added to the ball mill, water is added to the ball mill to keep the moisture content of the entire slurry system at 65~70%, and the mixture is ball-milled with bearing steel balls for 5~6 hours.

8. The method for preparing ferrite according to claim 6, characterized in that, In step S2, during the pressing and orientation forming process, filtration is carried out with a filter cloth to keep the moisture content of the formed blank at 10-15%.

9. The method for preparing ferrite according to claim 6, characterized in that, In S3, the sintering temperature is 1210℃ and the sintering time is 45min.

10. The use of the ferrite according to any one of claims 4 or 5 in permanent magnet materials.

Citation Information

Patent Citations

  • Method for improving grinding efficiency of permanent magnetic ferrite pre-sintering material

    CN110975996A

  • Preparation process of strontium ferrite pre-sintering material

    CN116178002A